2002
DOI: 10.1128/jvi.76.13.6845-6851.2002
|View full text |Cite
|
Sign up to set email alerts
|

A Tyrosine-Based Motif in the Cytoplasmic Tail of Pseudorabies Virus Glycoprotein B Is Important for both Antibody-Induced Internalization of Viral Glycoproteins and Efficient Cell-to-Cell Spread

Abstract: Pseudorabies virus (PRV), a swine alphaherpesvirus, is capable of causing viremia in vaccinated animals. Two mechanisms that may help PRV avoid recognition by the host immune system during this viremia are direct cell-to-cell spread in tissue and antibody-induced internalization of viral cell surface glycoproteins in PRV-infected blood monocytes, the carrier cells of the virus in the blood. PRV glycoprotein B (gB) is crucial during both processes. Here we show that mutating a tyrosine residue located in a YXX⌽… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
62
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 41 publications
5
62
2
Order By: Relevance
“…In both PRV-and HSV-infected cells, efficient capping has been shown to depend on the presence of viral protein gE, whereas internalization has been demonstrated to be initiated mainly by viral proteins gB and gD and to a lesser extent gE (8,10,39). Exactly how these viral proteins initiate the redistribution processes is not fully understood, but it has been shown that tyrosine-based amino acid motifs in the cytoplasmic tails of PRV gB and gE are of crucial importance for internalization and capping, respectively (7,9). In addition, PRV gE-mediated capping has been suggested to require specific tyrosine kinase signaling (9).…”
Section: Pseudorabies Virus (Prv) Is a Swine Alphaherpesvirus That Ismentioning
confidence: 99%
“…In both PRV-and HSV-infected cells, efficient capping has been shown to depend on the presence of viral protein gE, whereas internalization has been demonstrated to be initiated mainly by viral proteins gB and gD and to a lesser extent gE (8,10,39). Exactly how these viral proteins initiate the redistribution processes is not fully understood, but it has been shown that tyrosine-based amino acid motifs in the cytoplasmic tails of PRV gB and gE are of crucial importance for internalization and capping, respectively (7,9). In addition, PRV gE-mediated capping has been suggested to require specific tyrosine kinase signaling (9).…”
Section: Pseudorabies Virus (Prv) Is a Swine Alphaherpesvirus That Ismentioning
confidence: 99%
“…PRV GS443 expresses VP26-green fluorescent protein (GFP) in a PRV Becker background (42). PRV HF22 is a gB-null strain that carries a kanamycin resistance cassette in the gB locus in a PRV Becker background (16). PRV 232 is a gB-null strain expressing VP26-GFP in a PRV Becker background; it was generated for this study by crossing PRV HF22 and PRV GS443 in gB-complementing cells.…”
Section: Cell Lines and Virus Strainsmentioning
confidence: 99%
“…In polarized epithelial cells, gB is targeted to the basolateral surface, presumably via interactions of its cytoplasmic tail with adaptor protein 1B. The basolateral sorting of gB is hypothesized to enhance the efficiency of direct cell-to-cell spread of the virus (16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The gB C terminus is one of the longest of the herpesvirus-encoded glycoproteins and contains important cellular-sorting signals and regulates virally induced membrane fusion (28). The role of the gB tail in regulating herpesvirus-induced membrane fusion is most apparent because many mutations that modulate fusion are located in the gB C terminus (23,24,(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). For EBV, the C terminus also contains domains that are important for cell fusion and the cellular localization of gB (8,21).…”
mentioning
confidence: 99%